MODERN COMBINATIONS DRESSING AND OZONE BAGGING TREATMENT REDUCES THE AMOUNT OF BACTERIA IN GRADE II DIABETICUM - Mardiyono Mardiyono; Djamaluddin Ramlan; M. Choiroel Anwar; Rr. Sri Endang Pujiastuti; Umi Margi Rahayu (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2019)
Diabetic ulcers are open sores on the skin layer to the dermis caused by hyperglycemia and neuropathy. Infection is a barrier to the wound healing process, the incidence of infection in wounds with modern treatments of hydrocolloid and hydrogel type dressings is still high. Ozone has high antibactericidal and antimicrobial properties, is able to penetrate bacterial capsid walls and is expected to kill bacteria on the wound surface.To find the right way to cure diabetic ulcers using a combination of modern methods of dressing and ozonetherapy bagging.Experimental, non-equivalent control group design pre test, post test, population and infinite sample of 25 respondents. Modern dressing used has antibacterial properties and ozone concentration of 60-100ug / ml for 15 minutes using a limb bag was carried out until the 13th day with five times the measurement of the number of bacterial colonies using themethod swab and colonicounter. Data processing using a computer system with the General Linear Model. There was an average difference in the number of bacterial colonies between groups (505.73 ± 172.069 vs 322.21 ± 132.778, p = 0.0061).A combination of modern dressing and ozonetherapy bagging can reduce the number of bacterial colonies and speed up the healing process of the inflammatory phase II diabetic ulcer so that it can be applied in nursing care for diabetic ulcer patients.